The Need For Sacrifice In Law Enforcement In John Grisham's The Racketeer (2012): A Sociological Approach - Agistina, Arum, Dr. M. Thoyibi, MS, Titis Setyabudi, S.S. M.Hum (2016)
This study is about The Need for Sacrifice in Law Enforcement (2012) which is analyzed by using Socilogical Approach. The objective of the study are to know what problem arising in law enforcement is, to analyze who becomes a barrier in law enforcement and to know how to people cope with the obstacle in law enforcement. The researcher concerns about law enforcement based on Socilogical approach by Swingewood and Laurensoon. This research belongs to qualitative research. The primary data of this research is The Racketeer by John Grisham's in 2012, while the secondary data of this research are take from other source likely essay, critics, comments, historical information, biography of John Grisham, website, internet and other information. The researcher draws three conclution in this research. First, problem arising in law enforcement consist of the unfair treatment, insufficient efidence and unproffesional administration. Second, those standing against law enforcement are corrupt lawyer, FBI agent, corrupt judge and prosecutor. Third, coping with the obstacle consists of the sufficient evidence and applying disciplene of legal officer. Keywords: The Racketeer, Sacrifice, Law Enforcement, Sociological Approach